Mycoplasma pneumoniae infection in a clinical setting. - Othman, Norlijah; Isaacs, David; Daley, Andrew J.; Kesson, Alison M. (Wiley-Blackwell., 2008)
Background: Mycoplasma pneumoniae infection predominantly affects the respiratory tract, although the other organs may also be involved. Previous studies compared the clinical features of patients with M. pneumonia pneumonia to other pathogens and these studies were predominantly adult case series rather than involving children. The objectives of the present study were to compare the clinical features, laboratory, and radiographic findings in children seropositive for M. pneumoniae infection with children tested for suspected M. pneumoniae infection who were seronegative.